STATUS HUKUM KRAMA DESA ADAT YANG BERALIH AGAMA HINDU TERKAIT TANAH KARANG DESA: (Studi Kasus Di Br. Gria Cucukan, Desa Selat, Klungkung) - I Made Suryawan (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
The status and function of customary lands causes land problems to be complex, which can be a source of visible legal and social problems in various forms of land disputes. Similarly, the land of the village yard did not escape from the dispute. There are several factors such as economic, social, customs, which lead to the occurrence of land disputes of the village yard, as well as by religious converts. This will cause two problems that is 1). Are religious converts still entitled to the reef land of the village? And 2). How to resolve in case of land coral reefs? Based on literature study it can be concluded that 1). For Krama Desa Adat who moved from Hinduism to another religion is automated rights and obligations as the lost village manners, including in terms of land occupied village coral and 2). Way of solving cases related coral village land are: the traditional village has the power to implement the rules awig apply through prajuru village by way of promoting consensus, and where they are not able to be completed in the presence of the leaders of the village which is authorized for it, and when it is not also can the case / dispute can be submitted to the authorities or the national legal domain.